ANALISIS STRATEGI MANAJEMEN RISIKO PADA AKTIVITAS TRADING FOREX DI PT AGRODANA FUTURES - Enike Novilia Shafitri; Supriyono Supriyono (STKIP Pesisir Selatan, 2025)
Foreign exchange trading (forex) is one of the investment instruments that has a high profit potential, but is also accompanied by great risks due to market fluctuations that are difficult to predict. In this context, the implementation of risk management is the main factor that determines business sustainability and protection of customer capital. PT Agrodana Futures as one of the futures brokerage companies in Indonesia has played an active role in the development of a safe and transparent online trading system for investors. The purpose of this research is to analyze the implementation of risk management strategies in forex trading activities carried out by PT Agrodana Futures, starting from the aspects of risk identification, mitigation, customer education, and the role of technology in supporting the effectiveness of the surveillance system. The research results show that PT Agrodana Futures has implemented a comprehensive risk management system through the integration of technology features such as stop loss, automatic margin call, real-time monitoring, and continuous customer education. These findings show that good risk management not only involves technology control, but also human factors and consistent education to maintain the sustainability of a healthy and responsible trading system. It is hoped that this research can provide a comprehensive picture of the best practices in risk management in the digital era.